The Educational responsibility bill (7420/2006): the attempt to legalize educational accountability in Brazil - Filipe, Fabiana Alvarenga [UNESP]; Bertagna, Regiane Helena [UNESP] (Univ Federal Santa Maria, 2023)
Accountability or educational liability, so debated in research, is the main topic of this paper which is the result of a doctoral thesis that screened the 7420/2006 bill and its substitutes. PL 7420/2006 bill states about the quality of basic education and the liability of public officers for its fulfillment. Using documentary and bibliographic research, categories such as quality, assessment, participation and liability (as well as its extensions) surfaced from the bill were analyzed. The results of this research evince that even with movements towards resistance of hegemonic conceptions, the attempts of juridification of educational responsibility in Brazil is permeated with managerial views which seeks its foundations within neoliberal ideas and uses a democratic rhetoric to give it a participatory image. In this sense the outcomes of its outline might result in a reductionist conception entailed by blameworthiness of teaching professionals given its embedded logic.
Keywords: Liability; Large-scale assessment; Educational quality